Next Generation Natural Killer Cells for Cancer Immunotherapy - Rossi, Fiorella; Fredericks, Nathaniel; Snowden, Andrew; Allegrezza, Michael J.; Moreno-Nieves, Uriel Y. (Frontiers in Immunology, 2022)
In recent years, immunotherapy for cancer has become mainstream with several products now authorized for therapeutic use in the clinic and are becoming the standard of care for some malignancies. CAR-T cell therapies have demonstrated substantial efficacy for the treatment of hematologic malignancies; however, they are complex and currently expensive to manufacture, and they can generate life-threatening adverse events such as cytokine release syndrome (CRS). The limitations of current CAR-T cells therapies have spurred an interest in alternative immunotherapy approaches with safer risk profiles, and with less restrictive manufacturing constraints. Natural Killer (NK) cells are a population of immune effector cells with potent anti- viral and anti-tumor activity; they have the capacity to swiftly recognize and kill cancer cells without the need of prior stimulation. Although NK cells are naturally equipped with cytotoxic potential, a growing body of evidence shows the added benefit of engineering them to better target tumor cells, persist longer in the host and be fitter to resist the hostile tumor microenvironment (TME). NK cell-based immunotherapies allow for the development of allogeneic off-the-shelf products, which have the potential to be less expensive and readily available for patients in need. In this review, we will focus on the advances in the development of engineering of NK cells for cancer immunotherapy. We will discuss the sourcing of NK cells, the technologies available to engineer NK cells, current clinical trials utilizing engineered NK cells, advances on the engineering of receptors adapted for NK cells, and stealth approaches to avoid recipient immune responses. We will conclude with comments regarding the next generation of NK cell products, i.e., armored NK cells with enhanced functionality, fitness, tumor-infiltration potential, and with the ability to overcome tumor heterogeneity and immune evasion.